Metastatic melanoma of the gallbladder in a patient with acute cholecystitis: a case report and review of the literature - Sawyer, Emily; Tran, Kayla; Kalpakos, Lydia; Ratnayake, Sujith (International Surgery Journal, 2022)
Melanoma is an aggressive type of cancer that has significant metastatic potential. Most commonly, distant melanoma metastases are identified in the lung, liver and brain. Metastatic melanoma of the gallbladder is extremely rare and is usually associated with widespread gastrointestinal deposits which purports a poor prognosis. Whilst an uncommon site of melanoma metastases, it accounts for 50% of all tumour metastases to the gallbladder. There are a small number of case reports and case series that describe different manifestations of melanoma metastases to the gallbladder. We report the case of a patient who presented with acute cholecystitis on a background of cholelithiasis and underwent a laparoscopic cholecystectomy with histopathology identifying gallbladder metastasis from malignant melanoma.